Development of a model of a driver’s choice of speed considering the road conditions - Kulbashnaya, Nadezhda; Soroka, Konstantin (Eastern-European Journal of Enterprise Technologies, 2016)
The mathematical model of forming a driver’s controlling actions as for the choice of a motion speed on the adjacent road sections was developed. For the development, the methods of the theory of automatic regulation with the application of the transmission functions of a driver and a motor vehicle were used. The model of driving a motor vehicle by the motion speed channel for the drivers with a low level of the motivational perception which was supplemented by another inertia link characterizing the reaction of a driver to the road situation was accepted as a basic one. The value of the maximum entropy of a driver’s perception area was suggested as this characteristic. The periodic change of this parameter is considered on the sections with constant traffic conditions without any other traffic participants. This approach makes it possible to define how to arrange the road sections which follow one another to reduce to minimum the misalignance of a driver’s information load on them. The motion speed of a motor vehicle is obtained as the output value of the model. The margins of a change in the value of the maximum entropy and the limits of the value of speed corresponding to it were established. This makes it possible to simulate a driver’s reaction to a change in the road situation. With the help of the suggested model it is possible to assess the influence of the information content of the traffic environment on the results of a driver’s activity, which finally, makes it possible to develop the measures for regulating the parameters of a road situation and to influence a driver’s working conditions.